Phenotypic and genotypic characterisation of linezolid-resistant coagulase-negative staphylococci possessing cfr-carrying plasmid - Fei Jiang; Ziyan Kong; Ke Liu; Chen Cheng; Tingting Jiang; Ping Ma; Rongpeng Li (Journal of Global Antimicrobial Resistance, 2022)
ABSTRACT: Objectives: Linezolid-dependent growth has contributed to wide dissemination of Staphylococcus epidermidis in hospitals. This study aimed to characterise linezolid-resistant coagulase-negative staphylococci (CoNS) isolates and the possibility of linezolid dependence in China. Methods: Phenotypic and genotypic resistance of 13 CoNS isolates were investigated by antimicrobial susceptibility testing and PCR. Similarity of isolates was determined by pulsed-field gel electrophoresis (PFGE). Characterisation of the cfr-carrying plasmid was performed by S1 nuclease PFGE, Southern blotting and whole-genome sequencing (WGS). A maximum likelihood phylogenetic tree was constructed for phylogenetic analysis. Growth curve analysis was performed with and without linezolid to determinate the possible contribution of linezolid dependence to linezolid-resistant CoNS dissemination. Results: Thirteen CoNS isolates showed linezolid MICs of 8 mg/L to >256 mg/L, typed into three PFGE profiles. Southern blotting and WGS indicated that the cfr gene was located on a 39.5-kb plasmid with 99% identity to cfr-harbouring plasmids pSR01, pLRSA417 and pH29-46. The cfr gene was flanked by two copies of an IS256-like element ISEnfa4 family transposase, indicating the transferability of linezolid resistance conferred by the cfr gene. Comparative phylogenetic analysis revealed that Staphylococcus capitis XZ03 shared high similarity with linezolid-resistant S. capitis isolates in Huashan Hospital, Shanghai. Thirteen CoNS isolates did not exhibit linezolid dependence on exposure from 8–32 mg/L. Conclusion: The endemic CoNS clone carrying the cfr gene in our hospital showed high-level linezolid resistance, threatening linezolid use. Linezolid-dependent growth under linezolid selective pressure was not observed, indicating that it may not yet be a common phenotype in Staphylococcus spp.